Chapter Progettare attività di Public History: criteri orientativi ed indicazioni operative - Dati, Monica (Public History of Education. Teorie, esperienze, strumenti, 2022)
The contribution aims to serve as a toolkit to provide a sort of 'how to' guide on some aspects that public historians need to take into account when planning public history activities, from sources to content dissemination. Two short sections are therefore proposed, which schematically refer to the main stages of the public historian's work on two levels: 'research' and 'representation'.